THE ROLE OF THE BALI ELECTION SUPERVISORY BODY (BAWASLU) IN THE 2020 SIMULTANEOUS ELECTIONS - I Made Kartika; I Wayan Wiryawan; Adelia Paulina Pareira (International Journal of Education and Social Science Studies, 2024)
Regional Head Elections (Pilkada) are a real manifestation of democracy and are a means for the people to declare sovereignty. Pilkada organizers, especially in Bali Province, must work together to face the challenges and risks of the 2020 Pilkada on December 9. Both Bawaslu and the Bali Provincial KPU have to work hard considering that the democracy party this time was held during the Covid-19 pandemic. The purpose of this study is to determine the role of the Bali election supervisory agency (Bawaslu) in the 2020 simultaneous regional elections. The aim of the research is to build a strong, independent, solid election monitoring apparatus and institution in Bali. Develop effective and efficient monitoring patterns and methods in Bali. The research method uses interview, observation and data collection methods with non-participatory observation, namely a type of observation where the researcher is not directly involved in any activity of the research subject. The results of this research showed that Bawaslu's role is an independent election monitor tasked with overseeing and guarding the Bali regional elections. Bawaslu supervises the implementation of elections by receiving complaints, handling cases of election administrative violations and election criminal violations. Bawaslu has the authority over reports relating to alleged violations of the implementation of laws and regulations concerning elections. Either election administration violations, money politics violations, or disputes over the election process.